Imagery Intervention for Developing internal Motivation and Sport Confidence of boxing Players - Solanki, Ajay (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The aim of the present study was to develop internal motivation and sport confidence of boxingplayers, through imagery intervention. The sample of the study comprised 12 interuniversity levelboxing players, between the age ranges of 18 to 24 years. Movement imageryQuestionnaire-Revised (Hall etal., 1997) was used to screen out the subjects, on the basis oftheir imagery ability. Intended motivation was measured through internal MotivationInventory (Ryan, 1982), and sport confidence was assessed though the Carolina Sprat ConfidenceInventory (Manzo, Silva and Mink, 2001). Multivariate Analysis of Variance (MANOVA) was used toanalyze the data. The findings revealed that the subjects, in post-intervention condition, scoredsignificantly higher on internal motivation. Sport confidence of the players also increased tosignificant level. However, the overall F-ratio for multivariate analysis was not found to besignificant. Findings of this study provide useful evidence that imagery intervention can be a usefulsource to develop internal motivation and sport confidence of boxing players, which may furtherenhance their sport performance.